Performance evaluation of border irrigation by using NLREG Model - Vishwakarma, Shewta; Garg, Sunil; Singla, Chetna; Biwalkar, Nilesh (The Indian Journal of Agricultural Sciences, 2012)
The study was conducted at Research Farm of Department of Soil and Water Engineering, Punjab Agricultural University, Ludhiana to determine the performance of border irrigation method during the year 2006–07. It was based on irrigation performance parameters, such as water application efficiency, water storage efficiency and water distribution efficiency. Irrigation performance parameters that measure the irrigation performance were studied and analyzed for their relationship to surface irrigation design variables, i e inflow rate, length of run, cut off time and depth with the help of non-linear regression (NLREG) model. Water application efficiency is the irrigation performance parameter that correlated well with the design variables as compared to other irrigation performance parameters for exponential function. The quadratic function was best fit between water application efficiency and relative yield as well as net returns.